تكييف العقوبة في التشريع الجزائري - كوثر عون الله; نعيمة غرايبية (My University, 2025)
Abstract With the evolution of the concept of punishment .its purposes changed from mere implementation to a means of treatement and refom . therefore . it became necessary to adopt a new penal policy aimed at implementing refom and rehabilitation programs . and thus reforming and socially reintegrating offenders. In light of the inevitability of reforming and modernizing . the justice sector . the Algerian legislator sought . unlike other penal legislation . to create new alternatives for implementing custodial sentences and re-adapt them . such as the conditional release system . the semi-freedom system . and the public service work system .etc. These alternatives are resorted to depending on the circumstances of the crime and the personality of the offender . and whenever the conditions stipulated in law 04/05 regulating prisons and the social reintegration of prisoners are met . Within the framework of activating systems for adapting punishment . the Algerian legislator assigned assigned this task to the judge enforcing the penalties . with the aim of embodying the principle of judicial intervention in supervising the implementation of the sentence . in conjunction with special bodies and committees . ............................ الملخص: بتطور مفهوم العقوبة تغيرت أغراضها من مجرد تنفيذ لها إلى وسيلة علاج وإصلاح، لذا بات من الضروري انتهاج سياسة عقابية جديدة غايتها تجسيد برامج الإصلاح والتأهيل وبالتالي إصلاح الجناة وإعادة إدماجهم اجتماعيا. وفي ظل حتمية إصلاح قطاع العدالة وعصرنته سعى المشرع الجزائري على باقي التشريعات العقابية الأخرى إلى استحداث بدائل جديدة لتنفيذ العقوبة السالبة للحرية وإعادة تكييفها كنظام الإفراج المشروط، نظام الحرية النصفية، ونظام العمل للنفع العام..إلخ. حيث يتم اللجوء إلى هذه البدائل تبعا لظروف الجريمة وشخصية الجاني وكلما توافرت الشروط المنصوص عليها في القانون05/04 المتعلق بتنظيم السجون وإعادة الإدماج الاجتماعي للمحبوسين. وفي إطار تفعيل أنظمة تكييف العقوبة أسند المشرع الجزائري هذه المهمة إلى قاضي تطبيق العقوبات بهدف تجسيد مبدأ التدخل القضائي في الإشراف على تنفيذ العقوبة بمعية جهات ولجان خاصة. .......................... Résumé : Avec l'évolution du concept de la peine, ses finalités ont changé : d’un simple instrument de répression, elle est devenue un moyen de traitement et de réinsertion. Il est donc devenu nécessaire d'adopter une nouvelle politique pénale visant à concrétiser des programmes de rééducation et de réinsertion, dans le but de réformer les délinquants et de les réintégrer socialement. Dans le cadre de la nécessité de réformer et de moderniser le secteur de la justice, le législateur algérien, à l’instar des autres législations pénales, a introduit de nouvelles alternatives à l’exécution des peines privatives de liberté, en les réadaptant. Parmi celles-ci : le régime de la libération conditionnelle, le régime de semi-liberté, ou encore le travail d’intérêt général, etc. Le recours à ces alternatives dépend des circonstances de l’infraction, de la personnalité du délinquant, et de la disponibilité des conditions prévues par la loi n°05-04 relative à l’organisation des établissements pénitentiaires et à la réinsertion sociale des détenus. Dans le cadre de la mise en œuvre des systèmes d’aménagement des peines, le législateur algérien a confié cette mission au juge de l’application des peines, afin de consacrer le principe de l’intervention judiciaire dans la supervision de l’exécution de la peine, en collaboration avec des organes et commissions spécialisées.
Keywords: Keywords- Reform and Rehabilitation programs – Alternatives to Punishment Conditioning Systems - Conditional release system The semi-freedom system – The juge enforcingthe penalties – Committees; الكلمات المفتاحية: برامج الإصلاح والتأهيل – بدائل أنظمة تكييف العقوبة – الإفراج المشروط – نظام الحرية النصفية – قاضي تطبيق العقوبات – لجان.; Mots-clés : Programmes de rééducation et de réinsertion – Alternatives d’aménagement des peines – Libération conditionnelle – Régime de semi-liberté – Juge de l’application des peines – Commissions.